Students’ opinions on the light pollution application - Cengiz Özyürek; Güliz Aydın (International Electronic Journal of Elementary Education, 2015)
The purpose of this study is to determine the impact of computer-animated concept cartoons and outdoor science activities on creating awareness among seventh graders about light pollution. It also aims to identify the views of the students on the activities that were carried out. This study used one group pre-test/post-test experimental design model with 30 seventh graders. The data in the study were collected via open-ended questions on light pollution and semi-structured interview questions. The open-ended questions on light pollution were administered as a pre-test and a post-test. After the post-test was administered, semi-structured interviews were conducted with seven students. The data collected from the open-ended questions and semi-structured interviews were qualitatively analysed and quotes from the students’ statements were included. Looking at the answers of the students to questions on light pollution, it was understood that the activities that were carried out were effective. Furthermore, all of the students that were interviewed made positive statements about the activities that were carried out.